2020
DOI: 10.1101/2020.06.04.20115923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pleiotropic effects of heterozygosity for theSERPINA1Z allele in the UK Biobank

Abstract: Homozygosity for the SERPINA1 Z allele causes alpha-1 antitrypsin deficiency, a rare condition that can cause lung and liver disease. However, the effects of Z allele heterozygosity on non-respiratory phenotypes, and on lung function in the general population, remain unclear. We conducted the largest population-based study to date to determine Z allele effects on >2,400 phenotypes using the UK Biobank study (N>303,353). We detected strong associations between heterozygosity and non-respiratory phenoty… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In a family-based study of the rs28929474 variant (Z allele) in SERPINA1, which leads to alpha-1 antitrypsin deficiency (AATD) and greatly increased risk of emphysema, there was a significant genotype-by-smoking interaction on FEV 1 30 . A strong smoking interaction of rs28929474 heterozygote status with ever-smoking on lung function and COPD has been reported in UK Biobank 31 . Genome-wide interaction studies have confirmed the interaction of smoking with rs28927474 on risk to COPD 11 , and identified gene-by-smoking interactions at several other loci [8][9][10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 88%
“…In a family-based study of the rs28929474 variant (Z allele) in SERPINA1, which leads to alpha-1 antitrypsin deficiency (AATD) and greatly increased risk of emphysema, there was a significant genotype-by-smoking interaction on FEV 1 30 . A strong smoking interaction of rs28929474 heterozygote status with ever-smoking on lung function and COPD has been reported in UK Biobank 31 . Genome-wide interaction studies have confirmed the interaction of smoking with rs28927474 on risk to COPD 11 , and identified gene-by-smoking interactions at several other loci [8][9][10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 88%
“…29 A strong smoking interaction of rs28929474 heterozygote status with ever-smoking on lung function and COPD has been reported in UK Biobank. 30 GWAS have confirmed the interaction of smoking with rs28927474 on risk to COPD, 11 and identified gene-bysmoking interactions at several other loci. [8][9][10][11][12][13][14] Recently, a study of incident COPD found evidence for a gene-by-smoking interaction, further supporting our findings and suggesting that the relationship of the PRS to other related phenotypes or outcomes may also interact with smoking or other measures.…”
Section: Tenth Decilementioning
confidence: 94%